DEGENERATED PANICLE AND PARTIAL STERILITY 1 (DPS1) encodes a cystathionine β‐synthase domain containing protein required for anther cuticle and panicle development in rice. Issue 1 (30th September 2019) - Zafar, Syed Adeel; Patil, Suyash B.; Uzair, Muhammad; Fang, Jingjing; Zhao, Jinfeng; Guo, Tingting; Yuan, Shoujiang; Uzair, Muhammad; Luo, Qian; Shi, Jianxin; Schreiber, Lukas; Li, Xueyong
Summary: Degeneration of apical spikelets and reduced panicle fertility are common reasons for low seed‐setting rate in rice ( Oryza sativa ). However, little is known about the underlying molecular mechanisms. Here, we report a novel degenerated panicle and partial sterility 1 ( dps1 ) mutant that showed panicle apical degeneration and reduced fertility in middle spikelets. dps1 plants were characterized by small whitish anthers with altered cuticle morphology and absence of pollen grains. Amounts of cuticular wax and cutin were significantly reduced in dps1 anthers. Panicles of dps1 plants showed an accumulation of reactive oxygen species (ROS), lower antioxidant activity, and increased programmed cell death. Map‐based cloning revealed that DPS1 encodes a mitochondrial‐localized protein containing a cystathionine β ‐ synthase domain that showed the highest expression in panicles and anthers. DPS1 physically interacted with mitochondrial thioredoxin proteins Trx1 and Trx20, and it participated in ROS scavenging. Global gene expression analysis in dps1 revealed that biological processes related to fatty acid metabolism and ROS homeostasis were significantly affected, and the expression of key genes involved in wax and cutin biosynthesis were downregulated. These results suggest that DPS1 plays a vital role in regulating ROS homeostasis, anther cuticle formation, and panicle development in rice.